2019
DOI: 10.20473/jn.v13i2.7824
|View full text |Cite
|
Sign up to set email alerts
|

Improving Self-Protection Knowledge Against Sexual Abuse by Using Dreall Healthy and Animation Video

Abstract: Introduction: The number of child sexual abuse cases in Indonesia are still high, including in Ogan Komering Ilir Regency, South Sumatera. One of the preventive effort that can be practiced is teaching them about children self-protection knowledge from sexual abuse through sexual education using appropriate methods and media, such as watching animated video and dreall healthy. The aim of this research was to determine difference in dreall healthy and animated video about sexual education toward children self-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…This shows that there is a significant difference between the pre-test (before the approach through the video method) and the post-test results (after being given an approach through the video method) because the significant value (2-tailed) < 0.05. Thus it can be concluded that there is a difference between children's knowledge after doing the pre-test (no intervention) and after doing the post-test (there is a video intervention) (Romantika et al, 2020;Pradita et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This shows that there is a significant difference between the pre-test (before the approach through the video method) and the post-test results (after being given an approach through the video method) because the significant value (2-tailed) < 0.05. Thus it can be concluded that there is a difference between children's knowledge after doing the pre-test (no intervention) and after doing the post-test (there is a video intervention) (Romantika et al, 2020;Pradita et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Kegiatan edukasi mengenai seksualitas, termasuk langkah-langkah pencegahan kekerasan seksual, perlu diberikan sejak dini kepada anak, baik melalui pendidikan formal di sekolah, maupun di rumah dan lingkungan sekitar melalui orang tua dan anggota masyarakat yang berinteraksi dengan anak-anak. Pendidikan seksual sejak dini dapat membantu anak-anak membangun defense mechanism untuk memberikan pemahaman dan apresiasi terhadap nilai berharga dari tubuh yang mereka miliki (Pradita et al, 2019).…”
Section: Pendahuluanunclassified
“…Pendekatan melalui permainan memiliki potensi untuk diadaptasi dalam pembelajaran anti kekerasan seksual. Pendekatan audio-visual yang interaktif, seperti pada game, dapat memfasilitasi keterbukaan dan lingkungan yang rileks yang dibutuhkan anak dalam pembelajaran anti kekerasan seksual [4]. Terlebih di era teknologi ini, permainan berbasis digital dapat dengan mudah dimainkan dan menarik minat anak-anak.…”
Section: Pendahuluanunclassified